Hydroxylated fullerene promotes fracture healing in ovariectomized combined type 2 diabetic mice - Yunpeng Hu; Linjie Feng; Jie Li; Fuyuan Cao; Xiaoli Hou; Wei Chen; Yimeng Zhang; Lei Xing; Jingyuan Gao; Liu Zhang; Ye Liu; Faming Tian (Journal of Orthopaedic Surgery and Research)
Abstract Background The aim of this investigation was to assess the interventional role of hydroxylated fullerene in this model by histological, imaging, and biomechanical means in order to inform the treatment of fracture healing in a population of menopausal women with type 2 diabetes mellitus (T2DM). Methods Sixty-four female 8-week-old C57BL/6 mice were randomly divided into four groups: fracture (F), OVX + fracture (OF), T2DM + OVX + fracture (DOF), and hydroxylated fullerene-treated DOF (DOFF). A closed fracture was established in the right tibia of each mouse, which was performed 8 weeks after undergoing ovariectomy (OVX) in the OF, DOF, and DOFF groups. Hydroxylated fullerene (5 mg/kg, every two days) was administered intraperitoneally to the DOFF group starting the day after fracture. The right tibias were collected at 7 and 28 days post-fracture. Results The systemic administration of hydroxylated fullerene significantly increased the microstructural parameters of the callus (including bone volume fraction [BV/TV] and connectivity density [Conn.D]), promoted BMP-2 expression and inhibited TNF-α expression in the callus at 7 days post-fracture, and increased the expression of type I collagen (COL1) and osteocalcin (OCN) in the callus at 28 days post-fracture. Conclusion Hydroxylated fullerene may improve fracture healing in this diabetic mouse model by reducing the inflammatory response and promoting osteogenesis. These results suggest that hydroxylated fullerene may act as a therapeutic agent for fracture healing.